Metabolic resilience of the Australasian snapper (Chrysophrys auratus) to marine heatwaves and hypoxia - Bowering, Lyvia R.; McArley, Tristan J.; Devaux, Jules B. L.; Hickey, Anthony J. R.; Herbert, Neill A. (Frontiers in Physiology, 2023)
Marine organisms are under threat from a simultaneous combination of climate change stressors, including warming sea surface temperatures (SST), marine heatwave (MHW) episodes, and hypoxic events. This e following study sought to investigate the impacts of these stressors on the Australasian snapper (Chrysophrys auratus),a finfish species of high commercial and recreational importance, -from the SNA1 stock, as the largest snapper fishery in Aotearoa New Zealand (SNA1). A MHW scenario was simulated from 21°C (current February SST average for north-eastern New Zealand) to a future predicted level of 25°C, with the whole-animal and mitochondrial metabolic performance of snapper in response to hypoxia and elevated temperature tested after following 1-, 10-, and 30-days of this thermal challenge. It was hypothesised that key indicators of snapper metabolic performance would decline after 1-day of MHW stress, but that partial recovery might arise as result of thermal plasticity after chronic (e.g., 30-day) exposures. In contrast to this hypothesis, snapper performance remained high throughout the MHW: 1) Aerobic metabolic scope increased after 1-day of 25°C exposure and remained high. 2) Hypoxia tolerance, measured as the critical O2 pressure and O2 pressure where loss of equilibrium occurred, declined after 1-day of warm-acclimation, but recovered quickly with no observable difference from the 21 o C control following 30-days at 25°C. 3) The performance of snapper mitochondria was also maintained, with oxidative phosphorylation respiration and proton leak flux across the inner mitochondrial membrane of the heart remaining mostly unaffected.Collectively, the results suggest that heart mitochondria displayed resilience, or plasticity, in snapper chronically exposed to 25ºC. Therefore, contrary to the notion of climate change having adverse metabolic effects, future temperatures approaching 25 o C may be well tolerated by C. auratus in Northern New Zealand. Even in conjunction with supplementary hypoxia, as 25 o C appears to represent a more metabolically optimal temperature for this species, including when experienced with supplementary hypoxia.